Analiz pokazatelej, charakterizujušcich techniceskoe masterstvo vysokokvalificirovannych legkoatletov v bege na 110 m s bar'erami - Mirzoev, O. M.; Klevtsov, S. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article presents various indicators that characterize the technical skills of participants in the final race of the XVII World Athletics Championships in the 110 m hurdles (2019, Doha, Qatar). To conduct a comparative analysis of individual indicators of barrier running technique, data on domestic athletes obtained on the basis of their performance at the Russian championship in 2018 and 2019 are provided. The entire hurdles distance is divided into several interconnected segments (sections). Special attention is paid to the number and length of running steps up to the 1st hurdle, when running between hurdles and at the finish line. As an example, the dynamics of the length of the running step is shown, depending on the number of steps performed before the first obstacle, as well as between the hurdles of one of the world`s strongest hurdlers S. Shubenkov, world champion 2019, G. Holloway (USA) and national champion K. Shabanov. There are also other data that allow us to supplement previously published materials in the scientific and methodological literature of various years.